Conservation of a Rubber Terrain Model Map from World War II. Issue 2 (1st May 2013) - Grieve, Susanne; Wittig, Nicole; Powell, Emily
<x xml:space="preserve">Abstract</x> The Battleship North Carolina, one of the most decorated American warships from the Second World War, is a floating museum designated as the state's WWII memorial to the 10, 000 men and women in all branches of services who gave their lives in battle. One of the unique items on loan to the museum's collection is a rubber terrain model map shown in three-dimensional relief. While this style of map was not uncommon during World War II, these model maps are historically significant and present new challenges for conservators to preserve both the original intent of the object and the material it is made of. Working closely with the curatorial staff, several objectives for the treatment were identified including methods for transporting the map through the tight bulkheads of the ship, accommodating the museum's unique storage needs, mitigating the deterioration factors of rubber, and ensuring the overall preventative measures would not impede the accessibility of the map. Addressing these treatment goals involved manufacturing a custom-made Plexiglas support to aid in transportation and transition from storage to display as well as to create an oxygen-free microclimate for the stabilization of the map's rubber components.